2022
DOI: 10.21272/bel.6(4).49-60.2022
|View full text |Cite
|
Sign up to set email alerts
|

Education and Business in Conditions of Coopetition: Bibliometrics

Abstract: The study of the relationship between education and business is a very relevant issue when education and business are key factors in developing and uplifting the economy. Education is the foundation for creating a business since the effective activity is impossible without a strong information base. The purpose of this research is a bibliographic review of scientific publications devoted to the relationship between business and education, based on materials indexed by the Scopus, Web of Science, and Mendeley d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Bolstering this international turn to market-driven, lifelong education, has been the explosion of the knowledge-intensive economy, including the rapid turnover of new information, technological innovations, and the perceived need to manage these shifts strategically [34,35]. Within state structures of "capitalist accumulation" [36], lifelong learning has seemingly become synonymous with knowledge and information acquisition, with little apparent critique of the dominant cultural power relations and interests underlying knowledge production.…”
Section: Lifelong Learningmentioning
confidence: 99%
“…Bolstering this international turn to market-driven, lifelong education, has been the explosion of the knowledge-intensive economy, including the rapid turnover of new information, technological innovations, and the perceived need to manage these shifts strategically [34,35]. Within state structures of "capitalist accumulation" [36], lifelong learning has seemingly become synonymous with knowledge and information acquisition, with little apparent critique of the dominant cultural power relations and interests underlying knowledge production.…”
Section: Lifelong Learningmentioning
confidence: 99%
“…Samoilikova et al ( 2022) investigated «businesseducation -science» coopetition, the transfer of innovations connected with it and their effect on sustainable development in general. Koibichuk et al (2022b) also studied the coopetition of education and business, especially bibliometric aspects. However, in the study by Cranson (2018), it is noted that the level of education of employees is not always a guarantee of a successful business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They focus on the need for economic policy in the field of adult education, which introduces adult education into the functioning of the economic mechanism, since earlier adult education was not considered by scientists as an economic good. Koibichuk et al (2022) emphasize that adult education increases the competitiveness of workers. Adult education enables workers to update their skills and knowledge or acquire new knowledge, making them more competitive in the labor market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Surmanidze et al (2022) note that a relatively low level of financial literacy was indicated; students do not understand that they need to increase their financial education and skills, which makes the current situation even more dramatic. Bibliometric analysis on the subject of the relationship between adult education and economic indicators was carried out also by Koibichuk et al (2022) and Strielkowski et al (2022). It was found that the researchers focus on funding educational innovation of business companies, and financial regulation was targeted on topics such as tax, monetary, budget, and investment instruments.…”
Section: Literature Reviewmentioning
confidence: 99%